Active material, negative electrode layer, battery and methods for producing same
An active material with internal voids in its primary particles addresses the volume change issue in silicon-based batteries, improving stability and performance by accommodating lithium and reducing structural strain.
Patent Information
- Application Number
- JP2022077968
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-05-11
AI Technical Summary
Silicon (Si) based active materials for batteries experience significant volume changes during charging and discharging due to its large theoretical capacity, which can lead to structural instability and performance degradation.
The development of an active material with voids inside its primary particles, specifically with pore diameters of 10 nm or less and a void volume of 0.015 cc/g or more, which helps to minimize volume changes during charging and discharging by accommodating lithium precipitation and reducing confining pressure.
The proposed active material effectively suppresses volume changes during charging and discharging, enhancing the stability and performance of batteries by maintaining a consistent structure and reducing the need for excessive confining pressure.
Smart Images

Figure 0007614137000004 
Figure 0007614137000005 
Figure 0007614137000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to active materials, negative electrode layers, batteries, and methods of making the same. [Background technology]
[0002] In recent years, the development of batteries has been actively carried out. For example, in the automobile industry, development of batteries for use in electric vehicles (BEVs) or hybrid electric vehicles (HEVs) is underway. In addition, Si is known as an active material used in batteries.
[0003] For example, Patent Document 1 discloses an all-solid-state battery system containing alloy-based negative electrode active material particles such as silicon particles. Meanwhile, Patent Document 2 discloses that it is theoretically possible to use silicon clathrate as the negative electrode active material of a lithium ion battery. Furthermore, Patent Documents 3 and 4 disclose active materials having a silicon clathrate II type crystal phase and having voids inside the primary particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-059534 A [Patent Document 2] US Patent Application Publication No. 2012 / 0021283 [Patent Document 3] Patent Publication No. 2021-158003 [Patent Document 4] Patent Publication No. 2021-158004 Summary of the Invention [Problem to be solved by the invention]
[0005] Silicon has a large theoretical capacity and is effective in increasing the energy density of batteries, but on the other hand, its volume changes significantly during charging and discharging.
[0006] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an active material that undergoes small volumetric change upon charging and discharging. [Means for solving the problem]
[0007] [1] 1. An active material containing Si, the active material having voids inside primary particles, the voids having a pore diameter of 10 nm or less and a void volume X of 0.015 cc / g or more.
[0008] [2] The active material according to [1], wherein the void volume X is 0.09 cc / g or less.
[0009] [3] The active material according to [1] or [2], wherein the pore volume Y of the pores having a pore diameter of 50 nm or less is 0.05 cc / g or more and 0.25 cc / g or less.
[0010] [4] The active material according to [3], wherein a ratio (X / Y) of the void volume X to the void volume Y is 0.17 or more and 0.41 or less.
[0011] [5] The active material according to any one of [1] to [4], wherein the pore volume Z of the pores having a pore diameter of 100 nm or less is 0.05 cc / g or more and 0.40 cc / g or less.
[0012] [6] The active material according to [5], wherein a ratio (X / Z) of the void volume X to the void volume Z is 0.10 or more and 0.34 or less.
[0013] [7] The active material according to any one of [1] to [6], wherein the active material has a silicon clathrate II type crystal phase.
[0014] [8] In the X-ray diffraction measurement using CuKα radiation, peak A located at 2θ=20.09°±0.50° and peak B located at 2θ=31.72°±0.50° were observed as peaks of the above-mentioned crystalline phase of the above-mentioned silicon clathrate II type. The intensity of the above-mentioned peak A was calculated as I A The intensity of the above peak B is I B The maximum intensity at 2θ = 22° to 23° is I M In this case, I A / I M is between 1.75 and 10, and I B / I M The active material according to [7], wherein the n-th order is 1.35 or more and 7 or less.
[0015] [9] The active material according to any one of [1] to [6], wherein the active material has a diamond-type Si crystal phase.
[0016]
[10] A negative electrode layer containing an active material containing Si, the active material having voids inside primary particles, the voids having a pore diameter of 10 nm or less and a void volume P of 0.015 cc / g or more.
[0017]
[11] The negative electrode layer according to
[10] , wherein the void volume P is 0.031 cc / g or less.
[0018]
[12] The negative electrode layer according to
[10] or
[11] , wherein the pores having a pore diameter of 50 nm or less have a pore volume Q of 0.035 cc / g or more and 0.11 cc / g or less.
[0019]
[13] The negative electrode layer according to
[12] , wherein a ratio (P / Q) of the void volume P to the void volume Q is 0.22 or more and 0.39 or less.
[0020]
[14] The negative electrode layer according to any one of
[10] to
[13] , wherein the pores having a pore diameter of 100 nm or less have a pore volume R of 0.053 cc / g or more and 0.16 cc / g or less.
[0021]
[15] The negative electrode layer according to
[14] , wherein a ratio (P / R) of the void volume P to the void volume R is 0.14 or more and 0.30 or less.
[0022]
[16] A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer is the negative electrode layer according to any one of
[10] to
[15] .
[0023]
[17] A method for producing an active material according to any one of [1] to [9], comprising: an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; and a silicon clathrate generation step of heating the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate type crystal phase, wherein a scavenger that captures Na in the Na-Si alloy is used in the silicon clathrate generation step.
[0024]
[18] A method for producing a negative electrode layer, comprising: an active material producing step of producing an active material by the method for producing an active material according to
[17] ; and an anode layer forming step of forming a negative electrode layer using the active material.
[0025]
[19] A battery manufacturing method comprising: an active material manufacturing step of manufacturing an active material by the method for manufacturing an active material according to
[17] ; and a negative electrode layer forming step of forming a negative electrode layer using the active material. Effect of the Invention
[0026] The present disclosure has an effect of providing an active material that undergoes small volumetric change upon charging and discharging. [Brief description of the drawings]
[0027] [Figure 1] FIG. 2 is a schematic perspective view illustrating a crystalline phase of Si. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Diagram 3] 1 is a flowchart illustrating a method for producing an active material in the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The active material, the negative electrode layer, the battery, and the methods for producing them according to the present disclosure will be described in detail below.
[0029] A. Active material The active material according to the present disclosure is an active material containing Si, has voids inside the primary particles, and has a large void volume X of voids having a pore diameter of 10 nm or less.
[0030] According to the present disclosure, since the void volume X is large, the active material has a small volume change due to charging and discharging. In the past research, the inventors have found that by increasing the void volume Z of the minute voids having a pore diameter of 100 nm or less, the collapse of the voids due to the press treatment can be suppressed. Furthermore, they have found that by increasing the void volume Y of the minute voids having a pore diameter of 50 nm or less, the collapse of the voids due to the press treatment can be significantly suppressed. After further research, they have found that the minute voids having a pore diameter of 10 nm or less can significantly suppress the collapse of the voids due to the press treatment, as well as the minute voids having a pore diameter of 50 nm or less, and are effective in suppressing the volume change due to charging and discharging. Specifically, by increasing the void volume X of the minute voids having a pore diameter of 10 nm or less, the filling rate of the precipitated Li in the voids can be increased, and the volume change due to charging and discharging can be effectively suppressed.
[0031] The active material in the present disclosure is usually in the form of particles. The active material may be primary particles or secondary particles formed by agglomeration of primary particles. In either case, the primary particles usually have voids inside.
[0032] The active material in the present disclosure preferably has many micropores with a pore diameter of 10 nm or less. Pores with a pore diameter of 10 nm or less can store precipitated Li at a higher filling rate than pores with a pore diameter of more than 10 nm, so that the increase in the confining pressure can be reduced. The pore volume (cumulative pore volume) X of the pores with a pore diameter of 10 nm or less is, for example, 0.015 cc / g or more, may be 0.0167 cc / g or more, may be 0.020 cc / g or more, may be 0.023 cc / g or more, or may be more than 0.0337 cc / g. On the other hand, the pore volume X is, for example, 0.09 cc / g or less. The pore volume X can be determined, for example, by mercury porosimeter measurement, BET measurement, gas adsorption method, 3D-SEM, and 3D-TEM. The measurement method of the pore volume other than the pore volume X is similar.
[0033] The active material in the present disclosure preferably has many micropores with a pore diameter of 50 nm or less. The pores with a pore diameter of 50 nm or less can further suppress the collapse of the pores by pressing, compared with the pores with a pore diameter of more than 50 nm and a pore diameter of 100 nm or less. The pore volume Y of the pores with a pore diameter of 50 nm or less is, for example, 0.05 cc / g or more, may be greater than 0.065 cc / g, may be 0.072 cc / g or more, may be 0.083 cc / g or more, or may be 0.10 cc / g or more. On the other hand, the pore volume Y may be, for example, 0.25 cc / g or less, or may be 0.22 cc / g or less.
[0034] It is preferable that the ratio (X / Y) of the void volume X to the void volume Y is large. X / Y is, for example, 0.17 or more, or may be 0.19 or more, or may be 0.21 or more. On the other hand, X / Y is, for example, 0.41 or less.
[0035] The active material in the present disclosure preferably has many micropores with a pore diameter of 100 nm or less. The pores with a pore diameter of 100 nm or less can suppress the collapse of the pores by pressing, compared to the pores with a pore diameter of more than 100 nm. The pore volume Z of the pores with a pore diameter of 100 nm or less is, for example, 0.05 cc / g or more, may be 0.07 cc / g or more, may be 0.10 cc / g or more, or may be 0.12 cc / g or more. On the other hand, the pore volume Z is, for example, 0.40 cc / g or less, may be 0.39 cc / g or less, or may be 0.35 cc / g or less.
[0036] It is preferable that the ratio (X / Z) of the void volume X to the void volume Z is large. X / Z is, for example, 0.10 or more, or may be 0.14 or more, or may be 0.16 or more. On the other hand, X / Z is, for example, 0.34 or less.
[0037] The active material in the present disclosure has voids inside the primary particles. The porosity is, for example, 4% or more, and may be 10% or more. The porosity is, for example, 40% or less, and may be 20% or less. The porosity can be determined, for example, by the following procedure. First, a cross section of an electrode layer containing an active material is taken by ion milling. The cross section is then observed with a SEM (scanning electron microscope) to obtain a photograph of the particles. From the obtained photograph, silicon parts and void parts are clearly distinguished using image analysis software, and the image is binarized. The areas of the silicon parts and void parts are determined, and the porosity (%) is calculated from the following formula. Porosity (%) = 100 × (area of void part) / ((area of silicon part) + (area of void part))
[0038] Specific image analysis and porosity calculation can be performed as follows. For example, Fiji ImageJ bundled with Java 1.8.0_172 (hereinafter referred to as Fiji) is used as image analysis software. A secondary electron image and a backscattered electron image of the same field of view are combined to create an RGB color image. Then, in order to remove noise from each pixel, the obtained RGB image is blurred using the "Median (filter size = 2)" function in Fiji. Next, Fiji is used to color-code the silicon and void areas in the SEM image, and the void volume is calculated from the area ratio of the silicon and void areas.
[0039] In RGB color imaging, since both the secondary electron image and the backscattered electron image are expressed in grayscale, for example, the brightness x of each pixel in the secondary electron image is assigned to the Red value, and the brightness y of the backscattered electron image is similarly assigned to the Green value. This results in an RGB image where, for example, R=x, G=y, B=(x+y) / 2 for each pixel.
[0040] Average diameter of primary particles (D 50 ) is, for example, 50 nm or more, may be 100 nm or more, or may be 150 nm or more. On the other hand, the average particle size of the primary particles (D 50 ) is, for example, 3000 nm or less, may be 1500 nm or less, or may be 1000 nm or less. In addition, the average particle diameter of the secondary particles (D 50 ) is, for example, 1 μm or more, may be 2 μm or more, or may be 5 μm or more. On the other hand, the average particle size of the secondary particles (D 50 ) is, for example, 60 μm or less, and may be 40 μm or less. 50 ) can be obtained, for example, by observation using a SEM. The number of samples is preferably large, for example, 20 or more, or may be 50 or more, or may be 100 or more.
[0041] The active material in the present disclosure preferably has a silicon clathrate type crystal phase. The silicon clathrate type crystal phase may be a silicon clathrate type I crystal phase or a silicon clathrate type II crystal phase. For example, FIG. 1(a) shows a silicon clathrate type II, and in such a silicon clathrate type crystal phase, a polyhedron (cage) including a pentagon or hexagon is formed by a plurality of Si elements. This polyhedron has a space inside that can contain metal ions such as Li ions. By inserting metal ions into this space, the volume change due to charging and discharging can be suppressed. In particular, in all-solid-state batteries, in order to suppress the volume change due to charging and discharging, it is generally necessary to apply a high confining pressure, but by using the active material in the present disclosure, the confining pressure can be reduced, and as a result, the size of the confining jig can be suppressed.
[0042] The active material in the present disclosure may or may not have a silicon clathrate II type crystalline phase. In the former case, the active material may have a silicon clathrate II type crystalline phase as the main phase. The "main phase" means that the peak belonging to the crystalline phase has the highest diffraction intensity among the peaks observed in the X-ray diffraction measurement. In addition, "not having a crystalline phase" means that the peak of the crystalline phase is not confirmed in the X-ray diffraction measurement.
[0043] The silicon clathrate II crystal phase usually belongs to the space group (Fd-3m). The silicon clathrate II crystal phase has typical peaks at 2θ=20.09°, 21.00°, 26.51°, 31.72°, 36.26°, and 53.01° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.
[0044] In the crystal phase of silicon clathrate type II, the peak at 2θ=20.09°±0.50° is defined as peak A, and the peak at 2θ=31.72°±0.50° is defined as peak B. The intensity of peak A is defined as I A and the intensity of peak B is I B On the other hand, the maximum intensity at 2θ = 22° to 23° is I M The range of 2θ=22° to 23° can be used as a reference because it is within the range in which no peaks of the crystal phase related to Si usually appear.
[0045] I A / I M The value of I is preferably greater than 1. A / I M When the value is 1 or less, it can be determined that the silicon clathrate II type crystal phase is not substantially formed. A / I M The value of I is, for example, 1.75 or more, and may be 1.80 or more. A / I M The value of is, for example, 10 or less, and may be 5 or less.
[0046] I B / I M The value of I is preferably greater than 1. B / I M When the value is 1 or less, it can be determined that the silicon clathrate II type crystal phase is not substantially formed. B / I M The value of is, for example, 1.35 or more, and may be 1.40 or more, while I B / I M The value of is, for example, 7 or less, and may be 4 or less.
[0047] The active material in the present disclosure may or may not have a silicon clathrate I type crystalline phase. In the former case, the active material may have a silicon clathrate I type crystalline phase as a main phase. The silicon clathrate I type crystalline phase usually belongs to the space group (Pm-3n). The silicon clathrate I type crystalline phase has typical peaks at 2θ=19.44°, 21.32°, 30.33°, 31.60°, 32.82°, 36.29°, 52.39°, and 55.49° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°.
[0048] The active material in the present disclosure may or may not have a diamond-type Si crystalline phase. As shown in FIG. 1(b), in the diamond-type Si crystalline phase, a tetrahedron is formed by a plurality of Si elements. Since the tetrahedron does not have a space inside that can encapsulate metal ions such as Li ions, the diamond-type Si crystalline phase is less likely to suppress volume changes due to charging and discharging than the silicon clathrate-type crystalline phase. On the other hand, the diamond-type Si crystalline phase has higher structural stability than the silicon clathrate-type crystalline phase.
[0049] The active material of the present disclosure may have a diamond-type Si crystalline phase as a main phase. The diamond-type Si crystalline phase has typical peaks at 2θ=28.44°, 47.31°, 56.10°, 69.17°, and 76.37° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°.
[0050] When peak C at 2θ = 28.44° ± 0.50° is observed as a peak of diamond-type Si crystal phase, the intensity of peak C is expressed as I C Let us assume that A / I Cis, for example, greater than 1, may be 1.5 or more, may be 2 or more, or may be 3 or more. B / I C The preferred range of is I A / I C The preferred range is the same as that of the above.
[0051] The composition of the active material in the present disclosure is not particularly limited, but may include Na x S 136 It is preferable that x is represented by (0≦x≦24). x may be 0 or may be greater than 0. On the other hand, x may be 20 or less, 10 or less, or 5 or less. The active material in the present disclosure may contain an inevitable component (e.g., Li). The composition of the active material can be determined by, for example, EDX, XRD, XRF, ICP, or atomic absorption spectrometry. The composition of other compounds can be measured in the same manner. In general, an unavoidable oxide film is formed on the surface of the active material. Therefore, the active material may contain a trace amount of O (oxygen). The active material may also contain a trace amount of C (carbon) derived from the manufacturing process.
[0052] The active material in the present disclosure is generally used in batteries. The active material in the present disclosure may be either an anode active material or a cathode active material, with the former being preferred. The present disclosure can also provide an electrode layer (anode layer or cathode layer) having the above-mentioned active material, and a battery having the electrode layer. Examples of methods for producing the active material include the methods described in "D. Method for producing active material" below.
[0053] B. Negative electrode layer The negative electrode layer in the present disclosure contains the above-mentioned active material.
[0054] According to the present disclosure, by using the above-mentioned active material, it is possible to obtain a negative electrode layer that undergoes little volume change due to charging and discharging.
[0055] The negative electrode layer is a layer containing at least a negative electrode active material. The negative electrode active material is the same as that described in "A. Active material" above. When a press process is performed during the manufacture of the negative electrode layer, the voids present inside the primary particles of the negative electrode active material may be crushed. In the negative electrode active material before the press process, if the void amount Z having a pore diameter of 100 nm or less is large, the voids are prevented from being crushed by the press process. Furthermore, if the void amount Y having a pore diameter of 50 nm or less is large, the voids are further prevented from being crushed by the press process. In addition, since the voids having a pore diameter of 10 nm or less can store the precipitated Li at a high filling rate, if the void amount X is large, the increase in the confining pressure is reduced.
[0056] The negative electrode active material contained in the negative electrode layer preferably has many micropores with a pore diameter of 10 nm or less. The pore volume P of the pores with a pore diameter of 10 nm or less is, for example, 0.015 cc / g or more, may be 0.017 cc / g or more, or may be 0.019 cc / g or more. On the other hand, the pore volume P is, for example, 0.031 cc / g or less.
[0057] The negative electrode active material contained in the negative electrode layer preferably has many micropores with a pore diameter of 50 nm or less. The pore volume Q of the pores with a pore diameter of 50 nm or less is, for example, 0.035 cc / g or more, or may be 0.04 cc / g or more, or may be 0.06 cc / g or more. On the other hand, the pore volume Q is, for example, 0.11 cc / g or less, or may be 0.10 cc / g or less.
[0058] It is preferable that the ratio (P / Q) of the void volume P to the void volume Q is large. P / Q is, for example, 0.22 or more, and may be 0.27 or more. On the other hand, P / Q is, for example, 0.39 or less.
[0059] The negative electrode active material contained in the negative electrode layer preferably has many micropores with a pore diameter of 100 nm or less. The pore volume R of the pores with a pore diameter of 100 nm or less is, for example, 0.053 cc / g or more, and may be 0.06 cc / g or more. On the other hand, the pore volume R is, for example, 0.16 cc / g or less, and may be 0.14 cc / g or less.
[0060] It is preferable that the ratio (P / R) of the void volume P to the void volume R is large. P / R is, for example, 0.14 or more, and may be 0.20 or more. On the other hand, P / R is, for example, 0.30 or less.
[0061] The proportion of the negative electrode active material in the negative electrode layer is, for example, 20% by weight or more, may be 30% by weight or more, or may be 40% by weight or more. If the proportion of the negative electrode active material is too small, there is a possibility that sufficient energy density cannot be obtained. On the other hand, the proportion of the negative electrode active material is, for example, 80% by weight or less, may be 70% by weight or less, or may be 60% by weight or less. If the proportion of the negative electrode active material is too high, there is a possibility that the ionic conductivity and electronic conductivity in the negative electrode layer are relatively decreased.
[0062] The negative electrode layer may contain at least one of an electrolyte, a conductive material, and a binder, as necessary. Examples of the electrolyte include the electrolytes described in "C. Battery 3. Electrolyte Layer" below. Examples of the conductive material include carbon materials, metal particles, and conductive polymers. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and Ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of the binder include rubber-based binders and fluoride-based binders.
[0063] The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less. The negative electrode layer in the present disclosure is generally used in batteries.
[0064] C.Battery Fig. 2 is a schematic cross-sectional view illustrating a battery according to the present disclosure. The battery 10 shown in Fig. 2 has a positive electrode layer 1, a negative electrode layer 2, an electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode current collector 4 that collects current from the positive electrode layer 1, and a negative electrode current collector 5 that collects current from the negative electrode layer 2. In the present disclosure, the negative electrode layer 2 is the negative electrode layer described above in "B. Negative Electrode Layer".
[0065] According to the present disclosure, by using the above-described negative electrode layer, a battery with small volume change due to charging and discharging can be obtained.
[0066] 1. Negative electrode layer The negative electrode layer in this disclosure is similar to the content described above in "B. Negative electrode layer," and therefore will not be described here.
[0067] 2. Positive electrode layer The positive electrode layer is a layer containing at least a positive electrode active material, and may contain at least one of an electrolyte, a conductive material, and a binder, as necessary.
[0068] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 , Li(Ni 0.5 Mn 1.5 )O4 and the like; and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0069] A coating layer containing a Li-ion conductive oxide may be formed on the surface of the oxide active material. This is because it can suppress the reaction between the oxide active material and a solid electrolyte (particularly a sulfide solid electrolyte). An example of the Li-ion conductive oxide is LiNbO3. The thickness of the coating layer is, for example, 1 nm or more and 30 nm or less. In addition, for example, Li2S can be used as the positive electrode active material.
[0070] The shape of the positive electrode active material may be, for example, particulate. 50 ) is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle diameter (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less. 50 ) can be calculated, for example, from measurements using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM).
[0071] The electrolyte, conductive material, and binder used in the positive electrode layer are the same as those described in "B. Negative electrode layer" above, and therefore will not be described here. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0072] 3. Electrolyte layer The electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolytic solution).
[0073] Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes, and organic polymer electrolytes such as polymer electrolytes. Examples of the sulfide solid electrolyte include solid electrolytes containing Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may further contain at least one of O element and halogen element. Examples of the halogen element include F element, Cl element, Br element, and I element. The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. Examples of the sulfide solid electrolyte include Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2.
[0074] The electrolyte preferably contains a supporting salt and a solvent. Examples of the supporting salt (lithium salt) of the electrolyte having lithium ion conductivity include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6, and organic lithium salts such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, and LiC(CF3SO2)3. Examples of the solvent used in the electrolyte include cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), and chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolyte preferably contains two or more kinds of solvents.
[0075] The thickness of the electrolyte layer is, for example, not less than 0.1 μm and not more than 1000 μm.
[0076] 4.Other configurations The battery in the present disclosure preferably has a positive electrode current collector that collects the positive electrode layer and a negative electrode current collector that collects the negative electrode layer. Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon.
[0077] The battery of the present disclosure may further include a restraining tool that applies a restraining pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer along the thickness direction. In particular, when the electrolyte layer is a solid electrolyte layer, it is preferable to apply a restraining pressure in order to form a good ion conduction path and an electron conduction path. The restraining pressure is, for example, 0.1 MPa or more, may be 1 MPa or more, or may be 5 MPa or more. On the other hand, the restraining pressure is, for example, 100 MPa or less, may be 50 MPa or less, or may be 20 MPa or less.
[0078] 5.Battery The type of battery in the present disclosure is not particularly limited, but is typically a lithium ion battery. The battery in the present disclosure may be a liquid battery containing an electrolytic solution as an electrolyte layer, or may be an all-solid-state battery having a solid electrolyte layer as an electrolyte layer. The battery in the present disclosure may be a primary battery or a secondary battery, but is preferably a secondary battery. This is because it can be repeatedly charged and discharged, and is useful, for example, as an in-vehicle battery.
[0079] The battery in the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a parallel-connected stacked battery) or a bipolar stacked battery (a series-connected stacked battery). The shape of the battery may be, for example, a coin type, a laminate type, a cylindrical type, or a square type.
[0080] D. Method of manufacturing active materials Fig. 3 is a flow chart illustrating a method for producing an active material according to the present disclosure. In the production method shown in Fig. 3, first, a Na source and a Si source are reacted to obtain a Na-Si alloy (alloying step). Next, the Na-Si alloy is heated to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate type crystal phase (silicon clathrate generation step). At this time, a scavenger that captures Na in the Na-Si alloy is used. This results in an active material having a large void volume X and a silicon clathrate type crystal phase.
[0081] According to the present disclosure, by using a specific scavenger in the silicon clathrate production process, it is possible to obtain an active material that exhibits small volume change upon charging and discharging.
[0082] 1.Alloying process The alloying step in the present disclosure is a step of reacting a Na source and a Si source to obtain a Na-Si alloy.
[0083] The Si source is a particle containing at least Si. The Si source may be a simple substance of Si or an alloy of Si and another metal. When the Si source is an alloy, the alloy preferably contains Si as a main component. The proportion of Si in the alloy is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more.
[0084] The Si source is preferably porous Si having many voids inside the primary particles. In the Si source, the void volume α of the voids having a pore diameter of 50 nm or less is, for example, 0.02 cc / g or more, and may be 0.05 cc / g or more, 0.10 cc / g or more, 0.11 cc / g or more, or 0.12 cc / g or more. On the other hand, the void volume α is, for example, 0.20 cc / g or less, and may be 0.19 cc / g or less. The BET specific surface area of the Si source is, for example, 20 m 2 / g or more, 25m 2 / g or more, 2 On the other hand, the BET specific surface area of the Si source may be, for example, 200 m 2 The average particle size of the Si source (D 50 ) is, for example, 0.5 μm or more and 10 μm or less.
[0085] As a method for producing a Si source (porous Si), for example, an alloy of Mg and Si (Mg-Si alloy) is produced, and then Mg is removed from the Mg-Si alloy. The Mg-Si alloy can be obtained, for example, by heating a mixture of Mg and Si. The ratio of Mg to Si (Mg / Si) is, for example, 1.0 or more, may be 1.5 or more, or may be 2.0 or more. On the other hand, Mg / Si is, for example, 6.0 or less. As a method for removing Mg from an Mg-Si alloy, for example, a method is included in which Mg in the Mg-Si alloy is changed to MgO by heating the Mg-Si alloy in an inert gas atmosphere containing oxygen, and then MgO is removed with an acid solution. As an acid solution, for example, an aqueous solution containing hydrochloric acid (HCl) and hydrogen fluoride (HF) is included.
[0086] Also, as a method for producing a Si source (porous Si), for example, there is a method of producing an alloy of Li and Si (Li-Si alloy) and then removing Li from the Li-Si alloy. The Li-Si alloy is obtained, for example, by mixing Li and Si. The ratio of Li to Si (Li / Si) is, for example, 1.0 or more, may be 2.0 or more, may be 3.0 or more, or may be 4.0 or more. On the other hand, Li / Si is, for example, 8.0 or less. As a method for removing Li from a Li-Si alloy, for example, there is a method of reacting the Li-Si alloy with a Li extractant. As the Li extractant, for example, there are alcohols such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, etc.; and acids such as acetic acid, formic acid, propionic acid, oxalic acid, etc.
[0087] In addition, examples of methods for producing a Si source (porous Si) include a method of producing an alloy of Mg and Si (Mg-Si alloy), then removing Mg from the Mg-Si alloy, then producing an alloy of Si and Li (Li-Si alloy) from which the Mg has been removed, and then removing Li from the Li-Si alloy.
[0088] On the other hand, the Na source contains at least Na. Examples of the Na source include metallic Na, NaH, and a metallic Na dispersion in which metallic Na particles are dispersed in oil.
[0089] As a method for obtaining a Na-Si alloy by reacting a Na source and a Si source, for example, a method of heating a mixture containing a Na source and a Si source can be mentioned. The heating temperature is, for example, 300°C or more, may be 310°C or more, may be 320°C or more, or may be 340°C or more. On the other hand, the heating temperature is, for example, 800°C or less, may be 600°C or less, or may be 450°C or less. In addition, the alloying step is preferably performed under an inert atmosphere such as an Ar atmosphere.
[0090] The Na-Si alloy preferably has a Zintl phase. The Zintl phase has typical peaks at 2θ=16.10°, 16.56°, 17.64°, 20.16°, 27.96°, 33.60°, 35.68°, 40.22°, and 41.14° in an X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, or within a range of ±0.30°. The Na-Si alloy preferably has a Zintl phase as a main phase. The Na-Si alloy may or may not have a silicon clathrate I type crystal phase.
[0091] The composition of the Na-Si alloy is not particularly limited, but may be any of the following: z S 136 It is preferable that the composition is represented by (121≦z≦151). z may be 126 or more, or 131 or more. On the other hand, z may be 141 or less. The Na-Si alloy may contain elements other than Na and Si. Examples of the other elements include Li, K, Rb, Cs, Ba, Ga, and Ge.
[0092] 2. Silicon clathrate production process The silicon clathrate generating step in the present disclosure is a step of heating the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate type crystal phase. The silicon clathrate type crystal phase may be a silicon clathrate I type crystal phase or a silicon clathrate II type crystal phase. By appropriately changing the heating conditions, a silicon clathrate I type crystal phase or a silicon clathrate II type crystal phase can be obtained. In addition, a scavenger that captures Na in the Na-Si alloy is used in the silicon clathrate generating step.
[0093] An example of the scavenger is a Na getter agent that reacts with Na vapor generated from the Na-Si alloy. The Na getter agent is disposed, for example, without contacting the Na-Si alloy. Examples of the Na getter agent include SiO, MoO3, and FeO. When using a Na getter agent, it is preferable that the silicon clathrate generation process is performed in a reduced pressure atmosphere.
[0094] Another example of the scavenger is a Na trapping agent that directly reacts with the Na-Si alloy to receive Na. The Na trapping agent is, for example, arranged in contact with the Na-Si alloy. Examples of the Na trapping agent include CaCl2, AlF3, CaBr2, CaI2, Fe3O4, FeO, MgCl2, ZnO, ZnCl2, and MnCl2. When using a Na trapping agent, the silicon clathrate generation process may be performed in a reduced pressure atmosphere or in a normal pressure atmosphere.
[0095] The heating temperature in the silicon clathrate production step is, for example, 100° C. or higher, and may be 200° C. or higher, or may be 270° C. or higher. On the other hand, the heating temperature is, for example, 500° C. or lower, and may be 400° C. or lower.
[0096] 3.Active material The active material obtained by each of the above steps has a silicon clathrate type crystal phase. The active material has voids inside the primary particles. The preferred range of the void amount of the active material is I. A / I M and I B / I M As for the preferred range of and other matters, the contents described above in "A. Active material" can be cited as appropriate.
[0097] E. Method of manufacturing the negative electrode layer The present disclosure provides a method for producing a negative electrode layer, the method including: an active material production step of producing an active material by the above-described active material production method; and an anode layer formation step of forming a negative electrode layer using the active material.
[0098] According to the present disclosure, by using the above-mentioned active material, it is possible to obtain a negative electrode layer with small volume change due to charging and discharging. The active material manufacturing process is the same as that described in "D. Method for manufacturing active material" above. In addition, the method for forming the negative electrode layer is not particularly limited, and a known method can be adopted. As a method for forming the negative electrode layer, for example, a method of applying a slurry containing at least the active material to a negative electrode current collector and drying it can be mentioned.
[0099] When forming the negative electrode layer, a pressing process may be performed to press the negative electrode layer in the thickness direction. Examples of the pressing process include roller pressing and flat plate pressing. In addition, the contents described in the above "B. Negative electrode layer" can be appropriately cited for preferred embodiments of the obtained negative electrode layer.
[0100] F. Battery manufacturing method The present disclosure provides a method for manufacturing a battery, including an active material manufacturing step of manufacturing an active material by the above-described active material manufacturing method, and a negative electrode layer forming step of forming a negative electrode layer using the active material.
[0101] According to the present disclosure, by using the above-mentioned active material, a battery with small volume change due to charging and discharging can be obtained. The active material manufacturing process and the negative electrode layer forming process are the same as those described in the above "D. Method for manufacturing active material" and "E. Method for manufacturing negative electrode layer". In addition, the method for forming the battery is not particularly limited, and a known method can be adopted. In addition to the active material manufacturing process and the negative electrode layer forming process, the battery manufacturing method in the present disclosure may have a positive electrode layer forming process for forming a positive electrode layer, an electrolyte layer forming process for forming an electrolyte layer, and an arrangement process for arranging the positive electrode layer, the electrolyte layer, and the negative electrode layer in this order. For preferred embodiments of the obtained battery, the contents described in the above "C. Battery" can be appropriately cited.
[0102] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0103] [Example 1] As the Si source, Si powder (Si powder without voids inside the primary particles, SIE23PB manufactured by Kojundo Kagaku) was prepared. Using this Si source and NaH as the Na source, a Na-Si alloy was produced. Note that the NaH used was previously washed with hexane. The Na source and the Si source were weighed out so that the molar ratio was 1.05:1, and mixed using a cutter mill. This mixture was heated in a heating furnace under an Ar atmosphere at 400°C for 40 hours to obtain a powdered Na-Si alloy.
[0104] The obtained Na-Si alloy was used, and further, AlF3 was used as a Na trapping agent to perform a silicon clathrate generation process by a solid phase method. The Na-Si alloy and AlF3 were weighed out to a molar ratio of 1:0.35, and mixed using a cutter mill to obtain a reaction raw material. The obtained powdered reaction raw material was placed in a stainless steel reaction vessel, and heated in a heating furnace under an Ar atmosphere at 310°C for 60 hours to cause a reaction. The obtained reaction product is considered to contain the target active material and NaF and Al as by-products. This reaction product was washed using a mixed solvent in which HNO3 and H2O were mixed in a volume ratio of 90:10. This removed the by-products in the reaction product. After washing, the mixture was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain a powdered active material.
[0105] [Example 2] Mg powder and Si powder were weighed out to a molar ratio of 2.02:1, mixed in a mortar, and reacted in a heating furnace under an Ar atmosphere at 580°C for 12 hours. The mixture was cooled to room temperature to obtain ingot-shaped Mg2Si. Mg2Si was pulverized at 300 rpm for 3 hours using a ball mill with zirconia balls of 3 mm diameter. The pulverized Mg2Si was then heated at 580°C for 12 hours in a heating furnace under the flow of a mixed gas of Ar and O2 mixed at a volume ratio of 95:5, to react the oxygen in the mixed gas with Mg2Si. The obtained reaction product is considered to contain Si and MgO. The reaction product was washed with a mixed solvent of H2O, HCl, and HF mixed at a volume ratio of 47.5:47.5:5. This removed the oxide film on the Si surface and the MgO in the reaction product. After washing, the mixture was filtered, and the filtered solid was dried at 120° C. for 3 hours or more to obtain powdered porous Si. An active material was obtained in the same manner as in Example 1, except that the obtained porous Si was used as the Si source instead of Si powder.
[0106] [Example 3] Metal Li and Si powder were weighed out to a molar ratio of 4:1, and mixed in a mortar under Ar atmosphere at room temperature for 0.5 hours to react with each other. Li4Si was obtained. The obtained Li4Si was reacted with ethanol under Ar atmosphere. The obtained reaction product is considered to contain Si and CH3CH2OLi. This reaction product was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain powdered porous Si. An active material was obtained in the same manner as in Example 1, except that the obtained porous Si was used as the Si source instead of Si powder. [Example 4] Powdered porous Si was obtained in the same manner as in Example 3. An active material was obtained in the same manner as in Example 1, except that the obtained porous Si was used as the Si source instead of Si powder, and the heating conditions after the addition of AlF3 were changed from 310°C and 60 hours to 310°C and 120 hours.
[0107] [Example 5] Powdered porous Si was obtained in the same manner as in Example 3. An active material was obtained in the same manner as in Example 1, except that the obtained porous Si was used as the Si source instead of Si powder, and the heating conditions after the addition of AlF3 were changed from 310°C and 60 hours to 290°C and 120 hours.
[0108] [Example 6] Powdered porous Si was obtained in the same manner as in Example 3. Using the obtained porous Si as the Si source instead of Si powder, an active material was obtained in the same manner as in Example 1. Thereafter, the obtained active material was washed by immersing it in an HF aqueous solution for 3 hours (HF washing).
[0109] [Example 7] Powdered porous Si (first porous Si) was obtained in the same manner as in Example 2. Powdered porous Si (second porous Si) was obtained in the same manner as in Example 3, except that the obtained first porous Si was used instead of Si powder. An active material was obtained in the same manner as in Example 1, except that the obtained second porous Si was used instead of Si powder as a Si source.
[0110] [Example 8] Second porous Si was obtained in the same manner as in Example 7. An active material was obtained in the same manner as in Example 1, except that the obtained second porous Si was used as the Si source instead of Si powder, and the heating conditions after the addition of AlF3 were changed from 310°C and 60 hours to 270°C and 120 hours.
[0111] [Example 9] An active material was obtained in the same manner as in Example 7. Thereafter, the obtained active material was washed by immersing it in an aqueous HF solution for 3 hours (HF washing).
[0112] [Example 10] Except for adjusting the amounts of metallic Li and Si powder used, porous Si was obtained in the same manner as in Example 3. The obtained porous Si was used as the active material.
[0113] [Comparative Example 1] Si particles were used as the Si source, and Na particles were used as the Na source. The Si particles and Na particles were mixed in a molar ratio of 1:1, placed in a crucible, sealed under an Ar atmosphere, and heated at 700°C to obtain a Na-Si alloy. The obtained Na-Si alloy was heated under vacuum (about 1 Pa) and 340°C to remove Na, and an intermediate having a silicon clathrate II crystal phase was obtained. The obtained intermediate and Li metal were weighed in a molar ratio of Li / Si=2.5 and mixed in a mortar in an Ar atmosphere to obtain an alloy compound. The obtained alloy compound was reacted with ethanol in an Ar atmosphere to form voids inside the primary particles, and an active material was obtained.
[0114] [evaluation] (XRD measurement) X-ray diffraction (XRD) measurements using CuKα radiation were performed on the active materials obtained in Examples 1 to 9 and Comparative Example 1. As a result, it was confirmed that all of the active materials had a silicon clathrate II type crystal phase as the main phase.
[0115] In addition, the intensity of peak A located near 2θ=20.09° in the silicon clathrate II crystal phase is I A The intensity of peak B located near 2θ = 31.72° is I B The maximum intensity at 2θ = 22° to 23° was defined as I M And I A / I M and I B / I M The results are shown in Table 1.
[0116] (Measurement of void volume) The void volume of the active materials obtained in Examples 1 to 10 and Comparative Example 1 was determined. A mercury porosimeter was used to measure the void volume. The measurement was performed in the range of 40 Å to 4,000,000 Å using a Pore Master 60-GT (Quanta Chrome Co.). Analysis was performed using the Washburn method. The results are shown in Table 1.
[0117] [Table 1]
[0118] As shown in Table 1, in Examples 1 to 10, the void volume X and the void volume Y were larger than in Comparative Example 1. In addition, in all of Examples 1 to 9 and Comparative Example 1, I A / I M and I B / I M was greater than 1, confirming that a silicon clathrate type II crystal phase was formed.
[0119] In Comparative Example 1, Si was subjected to clathration (Na alloying and Na desorption treatment) and then to porosity. In this case, if the amount of Li used in porosity is increased, the silicon clathrate II crystal phase may disappear, so the amount of Li used is limited. In contrast, in Examples 2 to 9, Si was subjected to porosity and then to clathration. In this case, the amount of Li used in porosity can be increased, and sufficient porosity can be achieved. On the other hand, if sufficiently porous Si is subjected to clathration at high temperature, minute voids may disappear. In contrast, in Examples 2 to 9, clathration is possible at low temperature by using a scavenger. As a result, it is presumed that the active materials obtained in Examples 2 to 9 have a large void volume X and void volume Y.
[0120] (Measurement of increase in confining pressure) All-solid-state batteries were fabricated using the active materials obtained in Examples 1 to 10 and Comparative Example 1 as negative electrode active materials in the following manner.
[0121] (1) Preparation of the negative electrode The obtained active material, sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), conductive material (VGCF), butyl butyrate solution containing 5% by weight of PVDF-based binder, and butyl butyrate were added to a polypropylene container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a negative electrode current collector (Cu foil, manufactured by UACJ) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100°C. This resulted in a negative electrode having a negative electrode current collector and a negative electrode layer.
[0122] (2) Preparation of the positive electrode The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, average particle size 6μm), sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), conductive material (VGCF), butyl butyrate solution containing 5% by weight of PVDF-based binder, and butyl butyrate were added and stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a positive electrode collector (Al foil, manufactured by Showa Denko) by the blade method using an applicator, and dried for 30 minutes on a hot plate at 100 °C. This resulted in a positive electrode having a positive electrode collector and a positive electrode layer. The area of the positive electrode was smaller than that of the negative electrode.
[0123] (3) Preparation of solid electrolyte layer A sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), a heptane solution containing 5% by weight of a butylene rubber-based binder, and heptane were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied onto a release sheet (Al foil) by the blade method using an applicator, and dried on a hot plate at 100°C for 30 minutes. This resulted in a transfer member having a release sheet and a solid electrolyte layer.
[0124] (4) Fabrication of all-solid-state batteries A solid electrolyte layer for bonding was placed on the positive electrode layer of the positive electrode, and the resultant was set in a roll press machine and pressed at 100 kN / cm and 165° C. This produced a first laminate.
[0125] Next, the negative electrode was set in a roll press machine and pressed at 60 kN / cm and 25°C. This resulted in a pressed negative electrode. Then, a solid electrolyte layer for bonding and a transfer member were arranged in order from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer on the transfer member were arranged so as to face each other. The obtained laminate was set in a planar uniaxial press machine and temporarily pressed at 100 MPa and 25°C for 10 seconds. Then, the release sheet was peeled off from the solid electrolyte layer. This resulted in a second laminate.
[0126] Next, the solid electrolyte layer for bonding in the first laminate and the solid electrolyte layer in the second laminate were arranged to face each other, and then set in a flat uniaxial press and pressed at 200 MPa and 120° C. for 1 minute to obtain an all-solid-state battery.
[0127] (5) Measurement of the increase in confining pressure The obtained all-solid-state battery was charged, and the increase in the confining pressure was measured. The test conditions were confining pressure (constant dimension) 5 MPa, charging 0.1 C, and cut voltage 4.55 V. The confining pressure at 4.55 V was measured, and the increase in the confining pressure from the state before charging was calculated. The results are shown in Table 2. The results of the increase in the confining pressure in Table 2 are relative values when the result of Comparative Example 1 is set to 100.
[0128] [Table 2]
[0129] As shown in Table 2, it was confirmed that the increase in confining pressure was smaller in Examples 1 to 10 than in Comparative Example 1. This is presumably because the negative electrode active materials obtained in Examples 1 to 10 have many minute voids with pore diameters of 10 nm or less.
[0130] (Measurement of void volume) Using the active materials obtained in Examples 1 to 3, 6, and 10 and Comparative Example 1, pressed negative electrodes were obtained in the same manner as described in the above "Measurement of the increase in confining pressure." The void volume of the negative electrode active material in the pressed negative electrode was determined. The method for measuring the void volume was the same as above. The results are shown in Table 3.
[0131] [Table 3]
[0132] As shown in Table 3, it was confirmed that, compared to Comparative Example 1, Examples 1 to 3, 6, and 10 had a larger amount of voids in the negative electrode active material after pressing. [Explanation of symbols]
[0133] 1 ... Positive electrode layer 2 ... Negative electrode layer 3...electrolyte layer 4...Positive electrode current collector 5...Negative electrode current collector 10...battery
Claims
1. An active material containing Si, The primary particles have voids inside. The pore volume X of the pores having a pore diameter of 10 nm or less is 0.015 cc / g or more; An active material, wherein the pore volume Y of the pores having a pore diameter of 50 nm or less is 0.05 cc / g or more and 0.25 cc / g or less.
2. 2. The active material according to claim 1, wherein a ratio (X / Y) of the void volume X to the void volume Y is 0.17 or more and 0.41 or less.
3. An active material containing Si, The primary particles have voids inside. The pore volume X of the pores having a pore diameter of 10 nm or less is 0.015 cc / g or more; An active material, wherein the pore volume Z of the pores having a pore diameter of 100 nm or less is 0.05 cc / g or more and 0.40 cc / g or less.
4. The active material according to claim 3 , wherein a ratio (X / Z) of the void volume X to the void volume Z is 0.10 or more and 0.34 or less.
5. An active material containing Si, The primary particles have voids inside. The pore volume X of the pores having a pore diameter of 10 nm or less is 0.015 cc / g or more; The active material has at least one of a silicon clathrate II type crystal phase and a diamond type Si crystal phase.
6. In an X-ray diffraction measurement using CuKα radiation, peak A located at 2θ=20.09°±0.50° and peak B located at 2θ=31.72°±0.50° were observed as peaks of the crystalline phase of the silicon clathrate II type, The intensity of the peak A is I A and the intensity of the peak B is I B The maximum intensity at 2θ = 22° to 23° is I M In this case, I A / I M is 1.75 or more and 10 or less, and I B / I M The active material according to claim 5 , wherein the n-th order is 1.35 or more and 7 or less.
7. The active material according to claim 1, wherein the void volume X is 0.09 cc / g or less.
8. A negative electrode layer containing an active material including Si, The active material has voids inside the primary particles, The pore volume P of the pores having a pore diameter of 10 nm or less is 0.015 cc / g or more, a pore volume Q of the pores having a pore diameter of 50 nm or less is 0.035 cc / g or more and 0.11 cc / g or less.
9. The negative electrode layer according to claim 8 , wherein a ratio (P / Q) of the void volume P to the void volume Q is 0.22 or more and 0.39 or less.
10. A negative electrode layer containing an active material including Si, The active material has voids inside the primary particles, The pore volume P of the pores having a pore diameter of 10 nm or less is 0.015 cc / g or more, a pore volume R of the pores having a pore diameter of 100 nm or less is 0.053 cc / g or more and 0.16 cc / g or less.
11. The negative electrode layer according to claim 10 , wherein a ratio (P / R) of the void volume P to the void volume R is 0.14 or more and 0.30 or less.
12. A negative electrode layer described in any one of claims 8 to 11, wherein the void volume P is 0.031 cc / g or less.
13. A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, A battery, wherein the anode layer is the anode layer according to any one of claims 8 to 11.
14. A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, A battery, wherein the anode layer is the anode layer of claim 12.
15. A method for producing an active material, comprising the steps of: The active material contains Si, has voids inside primary particles, and has a pore diameter of 10 nm or less, and a void volume X of the voids is 0.015 cc / g or more; The manufacturing method includes: an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; and a silicon clathrate generation step of heating the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate type crystal phase. In the silicon clathrate generating step, a scavenger that captures Na in the Na-Si alloy is used.
16. An active material production process for producing an active material by the active material production method according to claim 15; a negative electrode layer forming step of forming a negative electrode layer using the active material; A method for producing a negative electrode layer having the above structure.
17. An active material production process for producing an active material by the active material production method according to claim 15; a negative electrode layer forming step of forming a negative electrode layer using the active material; A method for manufacturing a battery having the above structure.
Citation Information
Patent Citations
Anode and secondary battery
JP2009016339A
Lithium ion secondary battery
JP2016039086A
All-solid battery system and method for manufacturing the same
JP2017059534A
Active material, battery and method for producing active material
JP2020087886A
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158003A